Development of Solar-Powered Automatic Pest Trap for Rice Cultivation Plants in Indonesia - Telaumbanua, Mareli; Khotimah, Khusnul; Wisnu, Febryan Kusuma; Rahmawati, Winda; Haryanto, Agus; Fil'aini, Raizummi (Journal of Engineering and Technological Sciences, 2025)
Rice is the main commodity processed into rice, as a staple food for the people of Indonesia. Pests and diseases can cause decreased production to crop failure. The method used by farmers is pest control by spraying chemical pesticides. However, chemical pesticides have serious impacts on plants, increased immunity for pests, increased chemical residues in crops that threaten human health, and environmental pollution. The objective of this study is to design an integrated high-tech trap that is effective, efficient, cost-effective, durable, safe, environmentally friendly (zero-emission), and low in operational costs, with the ultimate goal of enhancing farmers' income. This automatic pest trap embeds a microcontroller, infrared sensor, fan and solar panel. Observations were made on 4 tools, namely complete lures, yellow LED, lights and pheromones. Based on the observations, Scotinophara coarctata and Nilaparvata lugens were identified as the most commonly trapped insect pests in rice fields. The insect's fall speed was fast, namely 1 minute 4 seconds with good stability. Insect readings came in higher on the complete lure due to the combination of three lures, each of which has its own insect attraction. The effectiveness of insect capture on the complete automatic insect trap was the highest at 84.47%.